Habitat Suitability of Release Site for Javan Gibbon (Hylobates moloch) in Mount Malabar Protected Forests, West Java - Anton Ario; Agus Priyono Kartono; Lilik Budi Prasetyo; Jatna Supriatna (Institut Pertanian Bogor (IPB University), 2018)
The javan gibbon reintroduction program requires assessment of suitable habitat within release sites to assure the survival of released gibbons. We studied habitat suitability for javan gibbon beginning in April 2017, extending to June 2017 in the Mount Malabar Protected Forest (MMPF), West Java. The objectives of this study were to analyze the habitat suitability of the release site for javan gibbon in MMPF. Analysis of Geographical Information System (GIS) and Principal Component Analysis (PCA) approach were used to obtain habitat suitability values. Habitat suitability variables measured are elevation, Normalized Differential Vegetation Index (NDVI), Bareness Soil Index (BSI), distance from the road, farming, settlement, and open field. We found suitability valued areas consisting of high suitability covered 2,009.23 ha (22.31%), moderate suitability covered 2,497.46 ha (27.73%), and low suitability covered 4.499,65 ha (49.96%), from a total area ± 8.894,47 ha in MMPF.